Nilai Pendidikan Agama Hindu Dalam Upacara Rsi Gana Di Desa Sumita, Gianyar - Ida Ayu Dwidyaniti Wira (Jurusan Dharma Acarya STAHN-TP Palangka Raya, 2021)
In Hindu society, religious routines have become part of their lives. For example, the implementation of the Rsi Gana Ceremony in Sumita Village, Gianyar District, is a religious activity carried out because of the purpose to be achieved, namely, the purification of places that are considered dirty because of new developments or because of things that are considered strange and awkward. Rsi Gana is considered important to do in order to ask for safety, purity and serenity together. Worship is aimed at Ida Sang Hyang Widhi with his manifestation as Dewa Ganapati, which is believed by Hindus to be a deterrent from all forms of sekala and niskala obstacles. So indirectly religious routines as a media for public educators can always understand the meaning, and function of the structure of the Rsi Gana Ceremony concept carried out by yajamana. From the results found by determining observation techniques, interview techniques and document study techniques that have been used as methods used to help get accurate data results in the field, it can be answered from the formulation of the existing problem, namely how is the public perception of the Rsi Gana ceremony in the village. Sumita Gianyar: The community believes that the Rsi Gana ceremony is very important to carry out to maintain harmony and balance in nature, in order to neutralize negative forces that exist on a scale and niskala. Furthermore, how the implementation of the Rsi Gana ceremony can be seen in sequence, namely: Ngaturang piuning to Hyang Guru, Kawitan and Kahyangan Tiga, ngeruwak, ring sanggah solar ceremony, land writing, prayascita, mecaru, melaspas, meat cravings and finally ngentegang linggih. For the values ​​contained in the Rsi Gana ceremony, it can be found the values ​​of tattwa, ethics, togetherness ceremonies (social) and religion.